시맨틱 웹 기반 국방무기 다차원 정보 분석 시스템 - 최중환(Jung-Hwoan Choi); 박정호(Jeong-Ho Park); 김평(Pyung Kim); 이승우(Seungwoo Lee); 정한민(Hanmin Jung); 서동민(Dongmin Seo) (한국콘텐츠학회 논문지, 12(11), 2012)
As defense science and technology are developing, smart weapons are being developed continually. The collection and analysis of the future strategic weapon information from all over the world have become a greater priority because information sharing became active. So, a system to manage and analyze heterogeneous defense intelligence is required. Semantic Web is the next generation knowledge information management technology for integrating, searching and navigating heterogeneous knowledge resource. Recently, Semantic Web is wildly being used in intelligent information management system. Semantic Web supports the analysis with the high reliability because it supports the simple keyword search as well as the semantic based information retrieval. In this paper, we propose the semantic web based multi-dimensional information analysis system on the national defense weapons that constructs ontology for various weapons information such as weapon specifications, nations, manufacturers and technologies and searches and analyses the specific weapon based on ontology. The proposed system supports the semantic search and multi-dimensional information analysis based on the relations between weapon specifications. Also, our system improves the efficiency on acquiring smart weapon information because it is developed with ontology based on military experts' knowledge and various web documents related with various weapons and intelligent search service. 국방 과학기술의 발달에 따라 첨단 무기들이 지속적으로 개발되고 온라인을 통한 정보의 공유가 활발해지면서, 각국의 미래 전략무기 소요 제기를 위한 정보의 수집 및 분석의 중요성이 증가하고 있으며, 이를 위한 이종의 국방정보를 통합 관리 및 분석하는 시스템이 필요하다. 시맨틱 웹은 이종의 지식자원을 통합하고 검색 및 내비게이션 할 수 있는 차세대 지식정보 관리 기반 기술로 최근에는 지능형 시스템 구축에 활발하게 사용되고 있다. 시맨틱 웹은 단순 키워드 검색이 아닌 의미적으로 연관된 정보 검색을 제공하기 때문에 신뢰도 높은 분석 결과를 제공한다. 본 논문에서는 시맨틱 웹을 기반으로 무기 제원 정보를 중심으로 무기의 제조국, 개발 회사, 개발 현황 등 무기와 관련된 다양한 관련 정보를 온톨로지로 구조화하는 것은 물론, 관련 정보를 이용해서 무기를 효과적으로 검색 및 분석할 수 있는 국방무기 다차원 정보분석시스템을 제안한다. 제안한 시스템은 무기의 제원명과 제원의 상하위 관계를 이용해서 확장 검색 기능을 제공하며, 무기 관련 정보를 이용해서 다양한 경로로 무기정보에 접근할 수 있는 기능과 함께 무기체계에 따른 다양한 분석 기능도 제공한다. 또한 개발된 시스템은 무기 분야의 전문가 지식과 웹에서 수집된 무기 관련 정보를 온톨로지로 구축하고 지능화된 검색 서비스를 구현함으로써, 정보전 시대에 필요한 첨단 무기 정보 획득의 효율성을 제고한다.